PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN DOMPU - Abdul Suhud (Distribusi - Journal of Management and Business, 2017)
This research is an explanatory research which is empirical investigation, and the investigation did not control the variable directly, because the realization of these variables is basically no manipulation. Subject in this study were official of Departemen Education Youth dan Sports in Dompu Regency is divided into 5 unit with a population of as many as 87 people. Sampling was conducted using proportional random sampling technique, where in each part of the work unit taken some of its members in accordance with the size of the number of official. The number of samples used is 72 people. Data analysis was performed using multiple regression analysis to see the effect of education and training and degree of education on on performance of official.Based on the results of this study found that education and training and degree of education either partially or simultaneously affect to the performance on Official of Education, Youth and Sport in Dompu Regency so always maintain the performance of officials by providing opportunities for officials to participate in education and training of officials, and always recruit officials based on their degree of education and provide an opportunity to raise the degree of education is shown to have a significant influence on performance of official. Keywords : Education and training, performenace of official